(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Tatyana S. Borisova (Athens National University of I. Kapodistriya. Athens, Greece); Lyudmila V. Tabachenko (Southern Federal University. Rostov-on-Don, Russian Federation) The formation of nationally-oriented manuals that take into account the language world picture of students is one of the most urgent tasks of the modern methodology of teaching Russian as a foreign language. In this article, the authors proposed the basic principles of constructing this kind of manuals for studying one of the most complicated themes of Russian word formation – verbal prefix derivation – for students with native Greek. At this stage, the material selected by the authors is limited to verbal prefixes with spatial meaning. The study of the verb prefixes of the Russian language is proposed to be based on the basis of attracting derivational and morphemic correspondences from the native language of students. The presence of numerous verbal derivatives of a similar structure in the Greek language, conditioned both by the genetic connections of the Russian and Greek languages, and by derivational borrowing from the Old Slavonic language – calque, allows the Greek students to explain the functioning of the prefix mode of language expansion and the formation of the semantics of derivatives, to semantize a number of prefixes with spatial meaning based on language categories native to the learner’s language, as well as to develop the skill proper use of relevant phenomena in speech. This training material is proposed to be used within the course of the Russian as a foreign language (a subclass of grammar of RFL) in preparation for the first and second certification levels (В1 - В2), that is, in the second and third year of studies in accordance with the curricula of the Department of Russian Philology and Slavic Studies of Athens National University of I. Kapodistriya. Key words: Russian as a foreign language, national (Greek) methodical orientation, prefix word formation. DOI 10.23683/1995-0640-2017-3-216-227